Variation in training requirements within general surgery: comparison of 23 countries. Issue 4 (11th June 2020) - Whewell, H.; Brown, C.; Gokani, V. J.; Harries, R. L.
Abstract : Background: Many differences exist in postgraduate surgical training programmes worldwide. The aim of this study was to provide an overview of the training requirements in general surgery across 23 different countries. Methods: A collaborator affiliated with each country collected data from the country's official training body website, where possible. The information collected included: management, teaching, academic and operative competencies, mandatory courses, years of postgraduate training (inclusive of intern years), working‐hours regulations, selection process into training and formal examination. Results: Countries included were Australia, Belgium, Canada, Colombia, Denmark, Germany, Greece, Guatemala, India, Ireland, Italy, Kuwait, the Netherlands, New Zealand, Russia, Saudi Arabia, South Africa, South Korea, Sweden, Switzerland, UK, USA and Zambia. Frameworks for defining the outcomes of surgical training have been defined nationally in some countries, with some similarities to those in the UK and Ireland. However, some training programmes remain heterogeneous with regional variation, including those in many European countries. Some countries outline minimum operative case requirement (range 60–1600), mandatory courses, or operative, academic or management competencies. The length of postgraduate training ranges from 4 to 10 years. The maximum hours worked per week ranges from 38 to 88 h, but with no limit in some countries. Conclusion: Countries have specific and often differing requirements of their medical profession. Equivalence in training is granted on political agreements, not healthcare need or competencies acquired during training. Abstract : Many differences exist worldwide in postgraduate surgical training programmes. Countries have specific and often differing requirements of their medical profession. Equivalence in training is granted on political agreements, not healthcare needs or competencies acquired during training. Wide variation between countries Abstract : Antecedentes: Existen muchas diferencias entre los programas de formación quirúrgica de posgrado del mundo. El objetivo de este estudio fue proporcionar una visión general de los requisitos formativos en cirugía general en 23 países diferentes. Métodos: En cada uno de los países participantes, un colaborador recopiló datos de la página web del organismo oficial encargado de la formación, si era posible. La información incluyó: gestión, formación, competencias académicas y operatorias, cursos obligatorios, años de formación de postgrado (que incluía el período de internado), regulaciones sobre las horas de trabajo, proceso de selección para la formación y existencia de un examen final. Resultados: Se incluyeron los datos de Australia, Bélgica, Canadá, Colombia, Dinamarca, Alemania, Grecia, Guatemala, India, Irlanda, Italia, Kuwait, Países Bajos, Nueva Zelanda, Rusia, Arabia Saudita, Sudáfrica, Corea del Sur, Suecia, Suiza, Reino Unido, Estados Unidos de América y Zambia. En algunos países existen los marcos normativos para definir los resultados del programa de formación, con ciertas semejanzas a los del Reino Unido e Irlanda. Sin embargo, algunos programas de formación, incluso en muchos países europeos, son muy heterogéneos con variaciones regionales. Pocos países describen el número mínimo de procedimientos quirúrgicos (rango 60 a 1.600), los cursos obligatorios o competencias quirúrgicas, académicos o de gestión exigidos. La duración de la formación postgraduada osciló de los 4 a los 10 años. El número de horas trabajadas máximas por semana oscilaron entre 38 y 88, sin límite en algunos países. Conclusión: Cada país tiene unos requisitos específicos, a menudo diferentes, para la formación de sus médicos. La convalidación se otorga por acuerdos políticos, más que por las necesidades médicas o por las competencias adquiridas durante la formación.